The geography of climate change risk analysis at central banks in Europe - Csaba Burger; Dariusz Wójcik (Magyar Nemzeti Bank, 2023)
Incorporating climate change considerations in central bank decisions has been fraught with legal and technical controversies. Legal, because interpretations of central bank mandates in relation to sustainability has been widely cited as hurdles to the discussion of climate change; and technical, because no methodology used to exist to assess and to measure the impact of climate risks on financial stability. This paper first analyses the spatial and temporal process climate change-related risk analysis spread among central banks by text mining - counting relevant bigrams - in 941 European financial stability reports of 39 central banks in Europe. It then maps climate risk relevant references of these reports. The study argues that geographical proximity played a significant role in the spread of the climate friendly central bank mandate interpretations. It also shows that the ECB, together with representatives of EU national central banks and their technical know-how, played a pivotal role in turning an innovation from being a novel research method into an accepted analytical framework. At the beginning of 2023, it now paves the way a towards a Basel-conform banking regulation within the EU, which reflects climate change risks too.
Keywords: E58; Q54; G17; G21; L38; 330; financial geography; central bank mandates; climate change; financial stability; text mining; bigram search; fiduciary duty